Biochemical and Initial Structural Characterization of the Monocot Chimeric Jacalin OsJAC1 - Huwa, Nikolai (Int J Mol Sci, 2021)
The monocot chimeric jacalin OsJAC1 from Oryza sativa consists of a dirigent and a jacalin-related lectin domain. The corresponding gene is expressed in response to different abiotic and biotic stimuli. However, there is a lack of knowledge about the basic function of the individual domains and their contribution to the physiological role of the entire protein. In this study, we have established a heterologous expression in Escherichia coli with high yields for the full-length protein OsJAC1 as well as its individual domains. Our findings showed that the secondary structure of both domains is dominated by β-strand elements. Under reducing conditions, the native protein displayed clearly visible transition points of thermal unfolding at 59 and 85 °C, which could be attributed to the lectin and the dirigent domain, respectively. Our study identified a single carbohydrate-binding site for each domain with different specificities towards mannose and glucose (jacalin domain), and galactose moieties (dirigent domain), respectively. The recognition of different carbohydrates might explain the ability of OsJAC1 to respond to different abiotic and biotic factors. This is the first report of specific carbohydrate-binding activity of a DIR domain, shedding new light on its function in the context of this monocot chimeric jacalin.